Thermoluminescence study of polyminerals extracted from clove and marjoram for detection purposes - Marcazzo, Salvador Julian (2012)
Food irradiation is a widely employed technology for food treatment. Since in several countries no regulations prevail, it is difficult to detect whether food has been irradiated or not. Among different analytical methods the study of the thermoluminescent (TL) emission of polymineral extracted from food is one of the most useful physical identification method. The aim of this work is to analyze the TL properties of inorganic polyminerals extracted from commercial clove (Syzygium aromaticum L.) and marjoram (Origanum majorana L.) spices exposed to 60Co gamma radiation for detection purposes. The feasibility of using the TL method for irradiated food detection and absorbed dose determination is assessed.